2017
DOI: 10.3892/ol.2017.6228
|View full text |Cite
|
Sign up to set email alerts
|

Computed tomography and magnetic resonance imaging features of ovarian fibrothecoma

Abstract: Abstract. The aim of the present study was to investigate the imaging characteristics of ovarian fibrothecoma. The cases of 25 female patients with pathologically confirmed ovarian fibrothecomas were retrospectively reviewed. Tumor location, size, density, signal intensity, cystic degeneration, calcification, enhancement pattern and ascites were assessed by computed tomography (CT) (n=20) and magnetic resonance imaging (MRI) (n=5). Clinical and histological features were also evaluated. The results revealed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 20 publications
0
6
0
1
Order By: Relevance
“…OTCA–FTCA is often prone to secondary cystic transformation when the tumor volume is large. Some scholars have reported that the cystic transformation rate is 76% (19/25) ( 20 ), so the tumor often appears as a cystic–solid or cystic mass, which may be preoperatively misdiagnosed as OGCTs or other ovarian tumor. Other scholars have divided these tumors into solid, cystic, and cystic–solid masses according to the degree of the cystic component.…”
Section: Discussionmentioning
confidence: 99%
“…OTCA–FTCA is often prone to secondary cystic transformation when the tumor volume is large. Some scholars have reported that the cystic transformation rate is 76% (19/25) ( 20 ), so the tumor often appears as a cystic–solid or cystic mass, which may be preoperatively misdiagnosed as OGCTs or other ovarian tumor. Other scholars have divided these tumors into solid, cystic, and cystic–solid masses according to the degree of the cystic component.…”
Section: Discussionmentioning
confidence: 99%
“…Ovarian fibroma scan be imaged in various ways on a CT scan. Typical imaging features are well-demarcated, oval-shaped, unilateral solid tumors, the parenchyma of which shows isodensity, hypointense or isointense signal, and mild to moderate enhancement following contrast-medium injection [ 3 , 15 ]. The presence of ascites and pleural effusion advocates the diagnosis of Meigs syndrome, the differential diagnosis of which from cardiomyopathy can be very challenging [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Both types of tumors—sclerosing stromal tumor and thecoma-fibroma, belong to sex cord stromal tumors and consist of fibrous stroma, but are not synonymous [21] . Radiologically, fibroma is described to typically show low signal intensity on T1-weighted MR images, and marked hypointensity on T2-weighted images [3] ; the contrast medium enhancement of fibromas is heterogeneous and mild-to moderate [ 22 , 23 ]. The sclerosing stromal tumor also shows hypo- or isointensity, compared to normal muscles in T1-weighted images, and intermediate to low signal intensity in T2-weighted images; however, on postcontrast images, a typical early intensive peripheral enhancement with centripetal progression and hypovascularized central area is present [ 3 , 7 ].…”
Section: Discussionmentioning
confidence: 99%